Atrial flutter in young children - Meshkova, M.; Doronin, A.; Khanenova, V.; Rudenko, N. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The article analyzes our own experience of treatment of atrial flutter in children of younger age (up to 6 years old). The study group consisted of 18 consecutive patients. In all patients the sinus rhythm was restored with medication or electrical cardioversion. The medical cardioversion was performed in10 (55.6%) patients, for 5 (27.8%) patients we used delayed and for 3 (16.7%) patients – urgent electric cardioversion. In 2 (11.1%) patients there was a single recurrence of arrhythmia after the cancellation of antiarrhythmic therapy. In 1 (5.6%) patient with repeatedly recurring arrhythmia at the age of 4 years 9 months (weight 18 kg) we successfully performed a radiofrequency catheter ablation of the cava-tricuspid isthmus. There were no complications of the treatment. At present, none of the patients in the study group have a recurrence of atrial flutterwithout antiarrhythmic therapy.